Strategi Diplomasi PT Indofood dalam Ekspansi Produk Indomie di Nigeria - Muhamad Yassar Naufal Subagja; Camelia Aprilianti; Citra Sukma Dewi BR Saragi; Nur Annisa Quraessin (Universitas 45 Surabaya, 2025)
The expansion of PT Indofood Sukses Makmur through its flagship instant noodle product, Indomie, in the Nigerian market serves as an example of the successful strategy of economic and corporate diplomacy. This study aims to examine the strategic steps implemented by PT Indofood in entering the international market, particularly Nigeria. The method used is a qualitative approach with analysis of secondary data such as journals, reports, and other official sources. The research results show that the success of Indomie in Nigeria is supported by strategic collaboration with Tolaram Group, product adaptation to local tastes, and the implementation of corporate social responsibility (CSR) programs. In addition to increasing market share, this approach also contributes to local economic development through job creation and diversification of the manufacturing sector. However, PT Indofood faces challenges, including inadequate infrastructure, economic fluctuations, and competition from local products. To ensure business sustainability, continuous adaptation strategies are needed. This study highlights the importance of synergy between economic diplomacy and corporate diplomacy in supporting business expansion into international markets, while also strengthening bilateral relations between Indonesia and Nigeria.